EFhd2, a protein linked to Alzheimer’s disease and other neurological disorders - Irving E Vega (Frontiers in Neuroscience, 2016)
EFhd2 is a conserved calcium binding protein linked to different neurological disorders and types of cancer. Although EFhd2 is more abundant in neurons, it is also found in other cell types. The physiological function of this novel protein is still unclear, but it has been shown in vitro to play a role in calcium signaling, apoptosis, actin cytoskeleton and regulation of synapse formation. Recently, EFhd2 was shown to promote cell motility by modulating the activity of Rac1, Cdc42 and RhoA. Although EFhd2’s role in promoting cell invasion and metastasis is of great interest in cancer biology, this review focusses on the evidence that links EFhd2 to Alzheimer’s disease (AD) and other neurological disorders. Altered expression of EFhd2 has been documented in AD, Parkinson’s disease, Huntington’s disease, Amyotrophic Lateral Sclerosis, and schizophrenia, indicating that Efhd2 gene expression is regulated in response to neuropathological processes. However, the specific role that EFhd2 plays in the pathophysiology of neurological disorders is still poorly understood. Recent studies demonstrated that EFhd2 has structural characteristics similar to amyloid proteins found in neurological disorders. Moreover, EFhd2 co-aggregates and interacts with proteins with known neuropathological proteins, such as tau, C9orf72 and Lrrk2. These results suggest that EFhd2 may play an important role in the pathophysiology of neurodegenerative diseases. Therefore, the understanding of EFhd2’s role in health and disease could lead to decipher molecular mechanisms that become activated in response to neuronal stress and degeneration.